Semi-supervised learning - Chapelle, Olivier; Schölkopf, Bernhard 1968-; Zien, Alexander 1971- (The MIT Press, 2010)
In the field of machine learning, semi-supervised learning (SSL) occupies the middle ground, between supervised learning (in which all training examples are labeled) and unsupervised learning (in which no label data are given). Interest in SSL has increased in recent years, particularly because of application domains in which unlabeled data are plentiful, such as images, text, and bioinformatics. This first comprehensive overview of SSL presents state-of-the-art algorithms, a taxonomy of the field, selected applications, benchmark experiments, and perspectives on ongoing and future research. Semi-Supervised Learning first presents the key assumptions and ideas underlying the field: smoothness, cluster or low-density separation, manifold structure, and transduction. The core of the book is the presentation of SSL methods, organized according to algorithmic strategies. After an examination of generative models, the book describes algorithms that implement the low-density separation assumption, graph-based methods, and algorithms that perform two-step learning. The book then discusses SSL applications and offers guidelines for SSL practitioners by analyzing the results of extensive benchmark experiments. Finally, the book looks at interesting directions for SSL research. The book closes with a discussion of the relationship between semi-supervised learning and transduction.
Beziehunskennzeichnungen laut Einband: edited by Olivier Chapelle, Bernhard Schölkopf and Alexander Zien
Includes bibliographical references and index
Keywords: Apprentissage supervisé (Intelligence artificielle); Supervised learning (Machine learning); Überwachtes Lernen; Maschinelles Lernen